Effects of language proficiency on L2 motivational selves: A study of young Chinese language learners. (February 2020) - Wong, Yu Ka
Abstract: Based on the L2 Motivational Self System (L2MSS), influences of second language (L2) learners' performed and self-perceived proficiency on their intended efforts toward L2 learning were evaluated with regard to their ideal L2 self and ought-to L2 self. The participants were young Chinese language learners. A total of 121 grade-six ethnic minority students in Hong Kong took proficiency tests in listening and reading comprehension, rated their own Chinese proficiency, and responded to a L2MSS questionnaire. The results of structural equation modeling show that: (1) the students' self-perceived proficiency was substantially related to their performances, and the influence of performed proficiency on the L2 selves was mediated by self-perceived proficiency; (2) the influence of self-perceived proficiency on the ideal self was substantial, and that on the ought-to self was limited and negligible; and, (3) it was primarily through the mediation of the ideal self that self-perceived proficiency affected intended learning efforts and further achievement in proficiency. The findings suggest a critical role played by the students' self-perceived proficiency: it is a mediator of the influence of actual proficiency to motivation and a constituent part of the ideal self, which, in turn, promotes proficiency through intended efforts.